Comparações citogenéticas e morfométricas em espécies de Corydoras (Pisces, Siluriformes, Callichtyidae) da bacia do rio Iguaçu - Rocha, Rafael Henrique da (2016)
Siluriforms is one of the most significant orders and greater diversity of species in the Neotropics, being Corydoras genus with the highest number of species. This group has color patterns and external morphology very similar among species. In this context, the present study used the cytogenetics and morphometry to characterize and differentiate Corydoras carlae and Corydoras sp. B of the Iguassu River basin. The diploid number found was 46 chromosomes, with karyotype formula of 22m + 22sm + 2st, and NF equal to 92. The impregnation with silver nitrate showed two bearing-NORs chromosomes and fluorescent hybridization with 18S ribosomal probe confirmed this result, charactering simple NORs system for species. Furthermore, the 5S rDNA was co-located with the 18S rDNA for Corydoras carlae and Corydoras sp. B. However, Corydoras sp. B have an extra marking 5S rDNA, located in interstitial position on the short arm of one submetacentric chromosome. The heterochromatin constitutive was found in centromeric and pericentomeric regions for both species, but with differences in the bearing chromosomes. The morphometric traits showed morphological differences between the two species, provided by indices: body height / standard length; interorbital distance / length of the head; horizontal diameter of orbit / length of the head. The results demonstrate that although both species have the same diploid number,e same karyotype formula and simple NORs system, C. carlae e Corydoras sp. B are different how much the location of the heterochromatin constitutive and in the 5S rDNA number bearing chromosomes, and present morphological differences which distinguish the two species.